ʿAlī ibn Sahl Rabban aṭ-Ṭabarī's Health Regimen or "Book of the Pearl" : Arabic Text, English Translation, Introduction and Indices - aṭ-Ṭabarī, ʿAlī ibn Sahl Rabban, (Islamic Philosophy, Theology and Science. Texts and Studies ;, 2021)
"The Arabic treatise edited and translated here was written in the middle of the 9th century CE by ʻAlī ibn Sahl Rabban aṭ-Ṭabarī, a Christian convert to Islam and one of the most remarkable thinkers of his time. The text can be described as a manual towards the preservation of health, addressed directly to the ʻAbbāsid caliph al-Mutawakkil and his household. It represents not only the oldest extant specimen of its kind, but is also distinguished by its largely non-technical language, as well as by a narrative style that creates an unusual interface with classical Arabic prose literature. The Greek and Indian sources upon which aṭ-Ṭabarīrelied testify to the synthetic and inclusive character of early Islamic medicine"--